2006
DOI: 10.1038/nm1407
|View full text |Cite
|
Sign up to set email alerts
|

The antimicrobial peptide cathelicidin protects the urinary tract against invasive bacterial infection

Abstract: The urinary tract functions in close proximity to the outside environment, yet must remain free of microbial colonization to avoid disease. The mechanisms for establishing an antimicrobial barrier in this area are not completely understood. Here, we describe the production and function of the cathelicidin antimicrobial peptides LL-37, its precursor hCAP-18 and its ortholog CRAMP in epithelial cells of human and mouse urinary tract, respectively. Bacterial contact with epithelial cells resulted in rapid product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
534
2
9

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 563 publications
(566 citation statements)
references
References 44 publications
21
534
2
9
Order By: Relevance
“…Consistent with other data [6][7][8][9] , kidney also expressed different kinds of bactericidal substance ( Supplementary Fig. 6a).…”
Section: Lrrc19 Promotes Expression Of Antimicrobial Substancessupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with other data [6][7][8][9] , kidney also expressed different kinds of bactericidal substance ( Supplementary Fig. 6a).…”
Section: Lrrc19 Promotes Expression Of Antimicrobial Substancessupporting
confidence: 91%
“…7), a-defensin-5 (ref. 8) and cathelicidins 9 . In addition, C-type lectins such as Reg3 are also found in the epithelial cells 10 .…”
mentioning
confidence: 99%
“…Recent studies have shown that rather than being a passive barrier, the epithelium is an active participant in the host response to infection through not only the expression and production of proinflammatory cytokines and chemokines that recruit inflammatory cells to the site of infection, but also the expression of antimicrobial peptides and proteins (AMPs) such as b-defensins and LL-37 [30][31][32]. Consistent with previous study using synthetic TLR2 ligand Pam3Cys [18], we showed that saLP stimulated production of IL-6 and IL-8 in a concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of neutrophils by using anti-mouse RB6 antibodies was performed as previously described. 33 Briefly, mice received an intravenous injection of 100 g of anti-RB6 antibodies 1 day before bacterial inoculation. Control mice received equivalent amounts of isotype control antibodies in sterile PBS.…”
Section: Depletion or Inactivation Of Neutrophilsmentioning
confidence: 99%